Factors Influencing Repurchase Intention of Facemasks from Online Platforms - Dinesh Elango; Simon Nnaemeka Ajah (Universitas Prasetiya Mulya, 2022)
At the end of the year 2019, a viral and deadly pandemic hit the world, referred to as the COVID-19 crisis. Healthcare professionals recommend that wearing face masks diminishes the prevalence of COVID-19 at the population level, resulting in a slower pandemic spread. In the COVID 19 situation there is everyday requirement of face mask and other precautionary products in order to prevent the spread of virus in Bangkok, Thailand. The study examined the factors influencing the Repurchase intention of face mask from 401 valid respondents. Inferential analysis to analyse the strength of influence of the independent variables and intervening variable on Repurchase intention of facemask was also performed through multiple linear regression and simple linear regression. The findings showed that other than Perceived Ease of use, all other variables Perceived usefulness, Satisfaction, Perceived website Quality, Privacy, System Availability, Trust has a statistically significant influence on Repurchase intention.